Evolution of Public Financial Management in Bhutan - Tobgyel, Sonam (International Journal of Humanities and Education Development (IJHED), 2021)
The purpose of this paper is to assess how the Public Financial Management (PFM) in the country has evolved over the years. Public Financial Management refers to the sets of laws, rules, systems and processes used by sovereign nations, to mobilize revenue, allocate public funds, and undertake public spending, account for funds and audit results. An effective Public Financial Management (PFM) system are required to maximize the efficient use of resources, create the highest level of transparency and accountability in government finances and to ensure long term economic success. A strong public financial management system are essential to improve service delivery, poverty reduction and to achieve the Millennium Development Goals (MDGs). The evolution of public financial management system in the Royal Government of Bhutan (RGoB) had its grass roots in the efforts of the third hereditary king (1952 to 1972) to expand and modernize the structure of Government and of society itself. The paper covers the public financial management in Bhutan in a chronological sequence since 1950s until the present period. It provides the readers with information on how the PFM in the country has evolved over the decades to meet the needs of the changing time. The PFM landscape in the country has undergone sea change from the manual system to online-web-based system and will continue to improve and change for the betterment in keeping with the technological advancement in the world in the 21st century era.